2012
DOI: 10.1111/j.1365-2141.2012.09175.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of type I Gaucher disease associated with persistent thrombocytopenia after treatment with imiglucerase for 4–5 years

Abstract: SummaryThe characteristics of Gaucher disease (GD) associated with persistent thrombocytopenia despite imiglucerase enzyme therapy in type 1 GD (GD1) were investigated by retrospective analysis of International Collaborative Gaucher Group (ICGG) Registry data. The study involved 1016 GD1 patients with an intact spleen for whom date of diagnosis, therapy initiation, and platelet counts were known, and who received continuous imiglucerase therapy for 4 to 5 years. These patients were stratified by last platelet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 41 publications
1
18
1
Order By: Relevance
“…Cases of GD without thrombocytopenia are observed. These cytopenias are attributed to splenic sequestration and bone marrow infiltration, but a direct impact of the enzyme deficiency on immature hematopoietic cells has also been described [26,129]. The blood count may be normal in patients with a history of splenectomy.…”
Section: Laboratory Abnormalitiesmentioning
confidence: 99%
“…Cases of GD without thrombocytopenia are observed. These cytopenias are attributed to splenic sequestration and bone marrow infiltration, but a direct impact of the enzyme deficiency on immature hematopoietic cells has also been described [26,129]. The blood count may be normal in patients with a history of splenectomy.…”
Section: Laboratory Abnormalitiesmentioning
confidence: 99%
“…Therefore, changes in splenomegaly in response to proposed treatments including ASM ERT that are currently in clinical trial may be a reasonable surrogate marker for evaluating response with the possible exception of pulmonary function where the correlation with spleen volume seems less certain [69,70]. A poor correlation between splenomegaly and platelet count that was observed in patients with NPD-B was also documented in patients with GD1, particularly for spleen volumes greater than 12 multiples of normal [8].…”
Section: Niemann-pick Disease Types a And B (Npd-b Asm Deficiency)mentioning
confidence: 95%
“…Although there was a statistically significant inverse correlation between spleen volume and red blood cell and platelet counts presumably attributable to more pronounced hypersplenism, the actual changes in cell counts per "fold-increase" in spleen size were clinically unimportant. Similarly, a recent report from the International Collaborative Gaucher Registry and Amsterdam Medical Center demonstrated that although splenomegalic patients with Gaucher disease with volumes in excess of 2000 mL almost always have persistent moderate to severe decreases in platelet count, the magnitude of thrombocytopenia differs relatively little over a spleen volume range of 2000 -5000 mL [8].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The secondary outcomes include symptomatic bone manifestations with imaging confirmation, a composite of massive hepatomegaly or splenomegaly, severe anemia or thrombocytopenia, and individual components of the primary and secondary composite outcomes. Cut-off values for continuous parameter are set according to published guidelines or previous studies [28, 29]. …”
Section: Methodsmentioning
confidence: 99%